Sosiolek Bahasa Bali Berdasarkan Variabel Usia dan Etnik - I Nyoman Rauh Artana (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2018)
The study of dialectology focuses on language variations based on geographic variables or geographical dialects so that it is known as the study of dialectical geography or linguistic geography but in its development, the study of dialectology extends to language variants based on social variables resulting in social dialectology (Chmabers & Petyt 1980). The social dialects that arise from the layers of society cause variations in the pronunciation of a sound or word in a language. Bali in particular Denpasar is a small city with a heterogeneous society so that inevitably the contacts of the language of the settlers with native speakers. The occurrence of these influences is related to extralinguistic and linguistic factors (intralinguistik). The linguistic (extralinguistic) situation associated with the person to whom the speaker is speaking, the topic of conversation, and the impulse of the speaker, such as the urge to be parallel / acceptable in the use of language by other speakers of language is the social reason of a person using other language elements. In addition, the factor of readiness or ease of pronunciation of certain language elements is the language factor of a person using other language elements. Ethnic differences result in differences in sound or phonological systems that are adapted to give rise to a dialect. The existence of ethnic Javanese and ethnic Balinese on the island of Bali is characterized by phonological differences that occur in a speech or communication so that withoutintroducingourselveswealreadyknowtheoriginofthesespeakersfromJavaorfromBali.